Gas-Sensing Properties and Preparation of Waste Mask Fibers/ZnS Composites - Wang, Q. Y.; Wu, Z. F.; Zhang, M.; Qin, Z. J.; Wang, L.; Zhong, F. R.; Duan, H. M. (Journal of electronic materials, 2022)
To realize the resource utilization of waste mask fibers (MF), a layer of ZnS nanoparticles was grown on MF by a one-step hydrothermal method, and a MF/ZnS sensor was successfully prepared. This is the first time that resource utilization of MF has been combined with the development of a high-performance gas sensor. The MF/ZnS sensor showed high sensitivity and recoverability to target vapors at room temperature. Compared with ZnS powder loaded on a ceramic substrate, the MF/ZnS composite responses to four analytes have been improved by 8.4~35.2 times. In addition, the time for the MF/ZnS sensor to complete one response–recovery cycle for all four analytes was less than 30 s. This should be attributed to the high gas permeability of the MF substrate, which made the ZnS particles loaded on the MF more fully exposed to contact with the target vapors. This work not only provides a simple and low-cost method to optimize the sensing performance of gas sensors but also provides a new way for the resource utilization of MF. Graphic Abstract